Nutritive value of three fodder species at different stages of maturity - Kanak, AR; Khan, MJ; Debi, MR; Pikar, MK; Aktar, M (Bangladesh Journal of Animal Science, 2013)
An experiment was conducted to compare the nutritive value of three fodder species: Para (Brachiaria mutica Stapf.), German (Echinochloa crusgalli L.) and Dhal (Hymenachne pseudointerrupta C. Muell) at three different stages of maturity. The grasses were cultivated in 9 plots arranged in completely randomized design having three replications for each fodder. The area of each unit plot was 6 m x 6 m. Number of cuttings were 16,000 /hectare, where plant to plant distance was 16 cm and row to row distance was 16 cm. Equal amount of organic and chemical fertilizer were applied in all stages of maturity. The fodders were first harvested after 60 d of planting, second and third harvests were done after successive 60 d of re-growth. There was highly significant (p<0.01) variation on DM content among the three fodders in the first and third cuttings and significant (p<0.05) difference was observed in the second cutting. There was also significant (p<0.01) effect on Ash content in the first cutting. Significant difference at 1% and 5% level of probability was observed in NFE content in the third and second cutting, respectively. Crude fiber (CF) content was only significant (p<0.05) in the third cutting. Among the three grasses German grass showed higher value in the proximate components except EE and CP (non-significant) than other grasses. Para, German and Dhal grasses were differed insignificantly (p>0.05) in terms of IVOMD and ME content in all stages of maturity. The highest values (58.35, 59.97 and 61.92 %) of IVOMD were found in German grass compared to those of Para and Dhal grasses in all stages of maturity. The highest ME values (8.18 and 8.42 MJ/kg DM) were also found in German grass than other grasses in the second and third stages of maturity. From the above findings it may be concluded that among the three fodders, German grass showed the best result in respect of nutritive value. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14123 Bang. J. Anim. Sci. 2012. 41 (2): 90-95